The barrier capacitance of n-SnS2/n-CdIn2Te4 heterojunction - Grushka, O.G.; Chupyra, S. M.; Myslyuk, O.M.; Slyotov, O.M. (Physics and Chemistry of Solid State, 2022)
The results of the study of the electrical characteristics of the n-SnS2/n-CdIn2Te4, obtained by a method of deposition over optical contact, have been presented. It is shown that the current-voltage characteristics and the capacitance-voltage (C-V) characteristics are typical for an abrupt heterojunction. The frequency dependence of the C-V characteristic is established, namely, with increasing frequency of alternating voltage, the barrier capacitance decreases, which is due to the presence of intrinsic structural defects and related localized donor states in the band gap of CdIn2Te4. The obtained results are explained by the frequency-dependent recharging processes of deep donor centers.